Integrating Cognitive Behavioral Therapy and Neuropedagogy to Support ADHD in Inclusive Elementary Education - Erviana, Nita; Haenilah, Een Yayah; Abdurrahman, Abdurrahman; Maulina, Dina (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
Attention Deficit Hyperactivity Disorder (ADHD) affects attention regulation, behavioral control, and executive functioning, creating persistent challenges for inclusive elementary classrooms. This study developed and evaluated a classroom-implementable intervention that integrated Cognitive Behavioral Therapy (CBT) and neuropedagogical strategies to support students with ADHD in inclusive education. Using a Research and Development approach adapted from Borg and Gall, the study combined qualitative needs analysis, expert validation, and a limited mixed-method field evaluation in Bandar Lampung, Indonesia. Participants comprised 18 elementary students aged 6-11 years with identified ADHD characteristics, including 10 students in the intervention group and 8 students in the comparison group; three experts reviewed the prototype model. Data were collected through interviews, classroom observations, feasibility questionnaires, SNAP-IV, BRIEF, and classroom-based rubrics for academic attention and multiple-intelligence-related functioning. Across 12 sessions delivered over six weeks, the intervention group demonstrated substantially larger improvements than the comparison group. Mean SNAP-IV scores declined from 45.7 to 30.2 in the intervention group, compared with 43.8 to 41.6 in the comparison group. BRIEF Global Executive Composite scores decreased from 72.5 to 58.4 in the intervention group and from 70.1 to 68.9 in the comparison group. Academic attention increased from 60 to 75 in the intervention group, whereas the comparison group increased from 62 to 64. The multiple-intelligence composite increased from 55 to 70 in the intervention group and from 54 to 56 in the comparison group. Qualitative findings also indicated stronger task persistence, better impulse control, improved peer interaction, and more active classroom participation. The integrated model is therefore feasible and educationally promising for strengthening behavioral regulation and cognitive engagement among students with ADHD in inclusive elementary settings.